A bio-based nylon thermal insulation material and preparation method thereof
By using the formulation of modified fillers and anti-aging agents in nylon insulation materials, the problems of reduced sealing and reduced thermal insulation effect caused by aging of the material are solved, and the long-term stability and service life of the material are achieved.
Patent Information
- Application Number
- CN202411737706.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-11-29
AI Technical Summary
Existing nylon thermal insulation materials are prone to aging after long exposure to wind, sun, rain and ultraviolet rays, resulting in reduced sealing, weakened elasticity, reduced thermal insulation effect, and shortened service life.
A bio-based nylon thermal insulation material is used, and its formulation includes 75-85 parts of PA56, 25-35 parts of polyterephthalyl decediamine, 20-30 parts of modified filler, 1-2 parts of color masterbing, 0.5-1.5 parts of lubricant, 0.5-1.2 parts of anti-aging agent and 0.1-0.2 parts of crosslinking agent. Through the chemical action of the modified filler and anti-aging agent, the mechanical properties, dimensional stability, thermal insulation properties and anti-aging properties of the material are improved.
This material is not easy to age, can maintain sealing, elastic and thermal insulation properties for a long time, greatly extends its service life, and also has excellent hydrophobic properties.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and in particular relates to a bio-based nylon thermal insulation material and a preparation method thereof. Background Art
[0002] As a connecting component in door and window profiles, nylon insulation material plays a role in mechanical transmission in aluminum alloy profiles and steel profile doors and windows. Nylon insulation material, which is made of PA66 (polyhexamethylene adipamide, commonly known as nylon-66) and glass fiber composite material, has low thermal conductivity and a thermal conductivity coefficient similar to that of aluminum alloy profiles. Therefore, when nylon insulation material is inserted into aluminum alloy profiles, the two can always maintain good bonding and sealing, and the profiles have good heat insulation, sound insulation, energy saving and dust prevention effects.
[0003] However, the starting raw materials for producing PA66 resin materials mainly come from petroleum, and the existing petroleum resources are tight. Therefore, bio-based nylon, such as PA56 (polypentamethylene adipamide, commonly known as nylon 56), should be used as much as possible to replace PA66 to produce nylon insulation materials, thereby saving resources. In addition, since nylon insulation materials are exposed to wind, sun, rain and ultraviolet erosion all year round, they are prone to aging, cracking and other problems, which in turn lead to decreased sealing, decreased elasticity, and reduced insulation effect, and the service life of nylon insulation materials is greatly shortened. Therefore, it is urgent to design and prepare a hydrophobic bio-based nylon insulation material with good aging resistance to meet market demand. Summary of the invention
[0004] The purpose of the present invention is to overcome the defects of the prior art and provide a bio-based nylon thermal insulation material and a preparation method thereof.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A bio-based nylon thermal insulation material comprises the following raw materials in parts by weight: 75-85 parts of PA56, 25-35 parts of polydecane terephthalamide, 20-30 parts of modified fillers, 1-2 parts of masterbatches, 0.5-1.5 parts of lubricants, 0.5-1.2 parts of anti-aging agents, and 0.1-0.2 parts of cross-linking agents.
[0007] PA56 is a polymer formed by the polymerization of bio-based pentamethylenediamine and petroleum-based adipic acid. It has similar breaking strength and good mechanical properties to PA66. It also has the advantages of high strength and wear resistance, flame retardancy, and high color fastness. Therefore, it can replace PA66 as the raw material for nylon thermal insulation materials. In addition, pentamethylenediamine, the raw material for PA56, can be obtained through starch microbial fermentation, which reduces production costs and alleviates the pressure of shortage of petroleum resources.
[0008] The melting point of polydecane terephthalamide is 316°C. It has better stability in high temperature environments. It also has excellent chemical resistance and can remain stable in corrosive environments such as acids and alkalis. In addition, polydecane terephthalamide has low water absorption and good dimensional stability. It is not easy to deform when used in nylon insulation materials, thereby ensuring the sealing between the nylon insulation material and the aluminum alloy, and thus the heat insulation, sound insulation, energy saving and dustproof performance of the profile are more stable.
[0009] Furthermore, the modified filler is prepared by the following steps:
[0010] (1) 1-tetradecanol, 10% sodium hydroxide solution and chloroform were added to a dry three-necked flask, stirred evenly and heated to 75°C, then 3-perfluorooctyl-1,2-epoxypropane was slowly added, and the reaction was kept warm for 3 hours after the addition was completed. After the reaction was completed, it was cooled to room temperature, deionized water was added and allowed to stand for stratification. After the pH of the aqueous phase was measured to be neutral, the organic phase was dried with anhydrous magnesium sulfate, filtered, and the filtrate was distilled under reduced pressure to obtain intermediate 1; the amount ratio of 1-tetradecanol to 3-perfluorooctyl-1,2-epoxypropane was 25.1 g:27.8 mL;
[0011] Under heating and base catalysis conditions, the molar ratio of 1-tetradecanol and 3-perfluorooctyl-1,2-epoxypropane is controlled to be 1.1-1.2:1, and the -OH of 1-tetradecanol and the epoxy group of 3-perfluorooctyl-1,2-epoxypropane react. The reaction process is as follows:
[0012]
[0013] (2) Blow nitrogen through a dry three-necked flask to expel air and moisture from the flask, then add intermediate 1, KH570 (3-(methacryloyloxy)propyltrimethoxysilane), tetraisopropyl titanate and benzene, stir thoroughly and heat to 90°C for 24 h. After the reaction, cool to room temperature, distill under reduced pressure, wash with anhydrous ethanol three times, and dry at 80°C for 12 h. The entire process is carried out under nitrogen protection to obtain intermediate 2. The amount ratio of intermediate 1, KH570, tetraisopropyl titanate and benzene is 41.4 g:15.3 mL:0.05 g:200 mL.
[0014] Under the action of the catalyst tetraisopropyl titanate, the molar ratio of intermediate 1 and KH570 is controlled to be 1:1.05-1.1, and the hydroxyl group of intermediate 1 and the silane group of KH570 undergo the following chemical reaction. The reaction process is as follows:
[0015]
[0016] (3) Add glass fiber, hollow glass microspheres and deionized water into a three-necked flask, stir well, add acetic acid to adjust the pH to 4, and set aside; disperse intermediate 2 in DMF (N,N-dimethylformamide), stir well, and transfer into the above three-necked flask. After the transfer is complete, heat to 60°C and react for 2 h. After the reaction is completed, cool to room temperature and centrifuge. Take the precipitate and ultrasonically disperse it in anhydrous ethanol for 30 min. Finally, dry it at 80°C for 12 h to obtain a modified filler. The amount ratio of glass fiber, hollow glass microspheres, intermediate 2, deionized water and DMF is 20 g:4 g:2 g:250 mL:15 mL.
[0017] Glass fiber as a reinforcing material can improve the mechanical properties of nylon thermal insulation materials; hollow glass microspheres are beneficial to improving the dimensional stability of nylon thermal insulation materials and effectively improving the thermal insulation performance of nylon thermal insulation materials. However, both contain a large number of hydroxyl groups on their surfaces, which have poor compatibility with the other raw materials of nylon thermal insulation materials, and thus have low dispersion, and cannot fully play a role in improving the mechanical properties, dimensional stability and thermal insulation performance of nylon thermal insulation materials. Therefore, the intermediate 2 is added to the acidic solution of glass fiber and hollow glass microspheres. Under heating conditions, the silaneoxy groups on the surface of the intermediate 2 can be hydrolyzed and condensed to form chemical bonds with the hydroxyl groups on the surface of the glass fiber and the hollow glass microspheres to form cross-links, thereby preparing a modified filler. The surface energy of the modified filler is greatly reduced, so it can be evenly dispersed in the nylon thermal insulation material. In addition, the surface of the modified filler also contains lipophilic long carbon chains, ether bonds and hydrophobic fluorine atoms, which further increase the compatibility between the modified filler and the remaining raw materials in the nylon thermal insulation material. In addition, the double bonds on the surface of the modified filler can chemically react with the double bonds on the surface of the anti-aging agent under the action of the cross-linking agent, so that the modified filler and the anti-aging agent can be highly dispersed and stably present in the nylon thermal insulation material, maximizing their own effects and giving the nylon thermal insulation material excellent and stable mechanical properties, dimensional stability, thermal insulation properties and hydrophobic properties.
[0018] Furthermore, the masterbatch is one or more of carbon black, aniline black, titanium dioxide, and zinc oxide.
[0019] Furthermore, the lubricant is one or more of stearic acid, calcium stearate, zinc stearate, magnesium stearate, and ethylene bisstearamide.
[0020] Furthermore, the anti-aging agent is prepared by the following steps:
[0021] S1. Add 2,4-dihydroxybenzophenone, triethylamine and chloroform to a dry three-necked flask under nitrogen protection, stir evenly and heat to 80°C, then slowly add 3-chloro-2-chloromethyl propylene, keep warm for 3 hours after the addition is complete, distill under reduced pressure after the reaction is complete, purify by column chromatography (the eluent is a mixed solvent of benzene and ethyl acetate, and the volume ratio of benzene and ethyl acetate is 8:2), and distill under reduced pressure to obtain intermediate 3; the amount ratio of 2,4-dihydroxybenzophenone, 3-chloro-2-chloromethyl propylene, triethylamine and chloroform is 23g:11.6mL:14mL:250mL;
[0022] The molar ratio of 2,4-dihydroxybenzophenone and 3-chloro-2-chloromethylpropene is controlled to be 1.05-1.1:1, then -OH of 2,4-dihydroxybenzophenone and -Cl of 3-chloro-2-chloromethylpropene react, and the reaction process is as follows:
[0023]
[0024] S2. Under nitrogen protection, add N,N'-bis-(2,2,6,6-tetramethyl-4-piperidinyl)-1,6-hexanediamine, triethylamine and DMF into a dry three-necked flask, stir and dissolve, then heat to 90°C, slowly add 2,6-di-tert-butyl-4-bromomethylphenol, and then keep warm for 3 hours. After the reaction is completed, cool to room temperature and then distill under reduced pressure to obtain intermediate 4; the amount ratio of N,N'-bis-(2,2,6,6-tetramethyl-4-piperidinyl)-1,6-hexanediamine, 2,6-di-tert-butyl-4-bromomethylphenol, triethylamine and DMF is 39.5g:32.1g:14mL:240mL;
[0025] Triethylamine is used as an acid-binding agent, and the molar ratio of N,N'-bis-(2,2,6,6-tetramethyl-4-piperidinyl)-1,6-hexanediamine and 2,6-di-tert-butyl-4-bromomethylphenol is controlled to be 1:1.05-1.1. Then, -NH- of N,N'-bis-(2,2,6,6-tetramethyl-4-piperidinyl)-1,6-hexanediamine and -Br of 2,6-di-tert-butyl-4-bromomethylphenol undergo substitution reaction under heating. The reaction process is as follows:
[0026] S3. Under nitrogen protection, add intermediate 3, pyridine and DMF to a dry three-necked flask, stir to dissolve and then heat to 90°C, then slowly add intermediate 4, then keep warm and react for 4 hours. After the reaction is completed, cool to room temperature and then distill under reduced pressure to obtain an antioxidant; the dosage ratio of intermediate 3, intermediate 4, pyridine and DMF is 25.9g:49g:7.2mL:240mL.
[0027] Pyridine is used as an acid-binding agent to control the molar ratio of intermediate 3 to intermediate 4 to be 1.05-1.1:1. Under heating, -Cl of intermediate 3 and -NH- of intermediate 4 undergo substitution reaction. The reaction process is shown below:
[0028]
[0029] Anti-aging agents contain hindered phenol structure, hindered amine structure and benzophenone structure. In the hindered phenol structure, the hydroxyl group is restricted by spatial barriers, and the hydrogen atom can easily fall off from the original molecular structure, thereby achieving the effect of donating protons and combining with peroxyl radicals, alkyl radicals, hydroxyl radicals, etc., causing them to lose their original activity, resulting in the termination of the thermal oxidative aging reaction; the hindered amine structure achieves light protection by capturing free radicals, decomposing hydroperoxides, quenching singlet oxygen and capturing heavy metal ions, and the hindered amine structure has high light stability efficiency; after absorbing ultraviolet light, the ketone group and hydroxyl group in the benzophenone structure will form an internal hydrogen bond to form a chelate ring. After absorbing ultraviolet light energy, the molecule will undergo thermal vibration, the internal hydrogen bond will break, the chelate ring will open, and the ultraviolet energy will be converted into heat energy and released. The three structures work synergistically to give the nylon thermal insulation material excellent resistance to thermal oxidation aging and ultraviolet aging. In addition, there is a chemical reaction between the anti-aging agent and the modified filler. Therefore, the anti-aging agent can stably exist in the nylon thermal insulation material and fully play its role. Therefore, the nylon thermal insulation material of the present invention is not easy to age, can maintain sealing, elasticity and thermal insulation performance for a long time, and its service life is greatly extended.
[0030] Furthermore, the cross-linking agent is one or more of benzoyl peroxide, triallyl isocyanurate, dicumyl peroxide, and azobisisobutyronitrile.
[0031] A method for preparing a bio-based nylon thermal insulation material comprises the following steps:
[0032] The raw materials are weighed by weight and put into a mixer, fully stirred until mixed evenly, and then put into a twin-screw extruder, melt-mixed and extruded to obtain a bio-based nylon thermal insulation material.
[0033] The beneficial effects of the present invention are as follows: the modified filler containing glass fiber, hollow glass microspheres and rich fluorine atoms has good compatibility with other raw materials, and has chemical reaction with the anti-aging agent containing hindered phenol structure, hindered amine structure and benzophenone structure, so that the modified filler and the anti-aging agent can be highly dispersed and stably present in the nylon thermal insulation material, play their role to the maximum extent, and give the nylon thermal insulation material excellent and stable mechanical properties, hydrophobic properties and anti-aging properties, etc., and greatly extend its service life. DETAILED DESCRIPTION
[0034] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] Example 1: Preparation of modified filler, the specific steps are as follows:
[0036] (1) Add 25.1 g of 1-tetradecanol, 20 mL of 10% sodium hydroxide solution and 200 mL of chloroform to a 500 mL dry three-necked flask, stir evenly and heat to 75°C, then slowly add 27.8 mL of 3-perfluorooctyl-1,2-epoxypropane. After the addition is complete, keep the temperature to react for 3 h. After the reaction is completed, cool to room temperature, add deionized water and stand to separate. After the pH of the aqueous phase is measured to be neutral, take the organic phase and dry it with anhydrous magnesium sulfate, filter it, and distill the filtrate under reduced pressure to obtain intermediate 1;
[0037] (2) Nitrogen was blown into a 500 mL dry three-necked flask to expel air and moisture from the flask, and then 41.4 g of intermediate 1, 15.3 mL of KH570, 0.05 g of tetraisopropyl titanate and 200 mL of benzene were added. After sufficient stirring, the temperature was raised to 90 °C for reaction for 24 h. After the reaction was completed, the mixture was cooled to room temperature, distilled under reduced pressure, washed with anhydrous ethanol for 3 times, and dried at 80 °C for 12 h. The entire process was carried out under nitrogen protection to obtain intermediate 2.
[0038] (3) Add 20 g of glass fiber, 4 g of hollow glass microspheres and 250 mL of deionized water into a 500 mL three-necked flask, stir well, and then add acetic acid to adjust the pH to 4 for later use; disperse 2 g of intermediate 2 in 15 mL of DMF, stir well, and then transfer to the above three-necked flask. After the transfer is completed, heat to 60 °C and react for 2 h. After the reaction is completed, cool to room temperature and centrifuge. Take the precipitate and ultrasonically disperse it in anhydrous ethanol for 30 min. Finally, dry it at 80 °C for 12 h to obtain a modified filler.
[0039] Example 2: Preparation of modified filler, the specific steps are as follows:
[0040] The remaining steps remain unchanged, except that the intermediate 2 in Example 1 is replaced by 3-aminopropyltrimethoxysilane to prepare a modified filler.
[0041] Example 3: Preparation of an anti-aging agent, the specific steps are as follows:
[0042] S1. Under nitrogen protection, add 23 g of 2,4-dihydroxybenzophenone, 14 mL of triethylamine and 250 mL of chloroform into a 500 mL dry three-necked flask, stir evenly and heat to 80°C, then slowly add 11.6 mL of 3-chloro-2-chloromethyl propylene, keep warm for 3 h after the addition is complete, distill under reduced pressure after the reaction is complete, purify by column chromatography (the eluent is a mixed solvent of benzene and ethyl acetate, the volume ratio of benzene to ethyl acetate is 8:2), and distill under reduced pressure to obtain intermediate 3;
[0043] S2, under nitrogen protection, add 39.5 g of N,N'-bis-(2,2,6,6-tetramethyl-4-piperidinyl)-1,6-hexanediamine, 14 mL of triethylamine and 240 mL of DMF into a 500 mL dry three-necked flask, stir to dissolve, heat to 90°C, slowly add 32.1 g of 2,6-di-tert-butyl-4-bromomethylphenol, and then keep warm for 3 h. After the reaction is completed, cool to room temperature, and then distill under reduced pressure to obtain intermediate 4;
[0044] S3. Under nitrogen protection, add 25.9 g of intermediate 3, 7.2 mL of pyridine and 240 mL of DMF into a 500 mL dry three-necked flask, stir to dissolve and then heat to 90°C, then slowly add 49 g of intermediate 4, then keep warm and react for 4 hours. After the reaction is completed, cool to room temperature and then distill under reduced pressure to obtain an anti-aging agent.
[0045] Example 4: Preparation of bio-based nylon thermal insulation material, the specific steps are as follows:
[0046] 75 parts of PA56, 25 parts of polydecane terephthalamide, 20 parts of the modified filler prepared in Example 1, 0.5 parts of carbon black, 0.5 parts of aniline black, 0.5 parts of magnesium stearate, 0.5 parts of the anti-aging agent prepared in Example 3, and 0.1 parts of diisopropyl peroxide were weighed and put into a blender, stirred thoroughly until mixed evenly, and then put into a twin-screw extruder, melt-mixed and extruded to obtain a bio-based nylon thermal insulation material.
[0047] Example 5: Preparation of bio-based nylon thermal insulation material, the specific steps are as follows:
[0048] 80 parts of PA56, 30 parts of polydecane terephthalamide, 28 parts of the modified filler prepared in Example 1, 1.5 parts of zinc oxide, 0.6 parts of stearic acid, 0.6 parts of ethylene bis stearamide, 1 part of the anti-aging agent prepared in Example 3, and 0.15 parts of azobisisobutyronitrile were weighed by weight and put into a blender, stirred thoroughly until mixed evenly, and then put into a twin-screw extruder, melt-mixed and extruded to obtain a bio-based nylon thermal insulation material.
[0049] Example 6: Preparation of bio-based nylon thermal insulation material, the specific steps are as follows:
[0050] 85 parts of PA56, 35 parts of polydecane terephthalamide, 30 parts of modified filler prepared in Example 1, 1 part of titanium dioxide, 1 part of zinc oxide, 0.75 parts of calcium stearate, 0.75 parts of zinc stearate, 1.2 parts of the anti-aging agent prepared in Example 3, 0.1 part of benzoyl peroxide, and 0.1 part of triallyl isocyanurate were weighed by weight and put into a mixer, stirred thoroughly until mixed evenly, and then put into a twin-screw extruder, melt-mixed and extruded to obtain a bio-based nylon thermal insulation material.
[0051] Comparative Example 1: Preparation of bio-based nylon thermal insulation material, the specific steps are as follows:
[0052] The remaining steps remain unchanged, only the modified filler of Example 4 is replaced by the modified filler prepared in Example 2, thereby preparing a bio-based nylon thermal insulation material.
[0053] Comparative Example 2: Preparation of bio-based nylon thermal insulation material, the specific steps are as follows:
[0054] The remaining steps remain unchanged, only the anti-aging agent in Example 4 is replaced by 0.3 parts of antioxidant 1076 and 0.3 parts of ultraviolet absorber UV-0, thereby preparing a bio-based nylon thermal insulation material.
[0055] Performance test: The bio-based nylon thermal insulation materials prepared in Examples 4-6 and Comparative Examples 1-2 were made into specimens according to the corresponding standards, and the tensile strength, elongation at break and flexural strength were tested, followed by dry heat aging and ultraviolet aging (dry heat aging conditions: dry heat aging at 105°C for 120h; ultraviolet aging conditions: at room temperature, a vertical irradiation distance of 20cm, under a 30W ultraviolet lamp, ultraviolet aging for 120h). After the aging, the tensile strength, elongation at break and flexural strength were tested again. The test results are shown in Table 1 below:
[0056] Table 1
[0057]
[0058] It can be seen from the test results of Comparative Example 1 and Example 4 that when the modified filler is replaced, there is no chemical reaction between it and the anti-aging agent, so the heat aging and ultraviolet aging resistance of the bio-based nylon thermal insulation material of Comparative Example 1 is significantly lower than that of Example 4; it can be seen from the test results of Comparative Example 2 and Example 4 that when the anti-aging agent is replaced with a common antioxidant and ultraviolet absorber without carbon-carbon double bonds, there is no chemical reaction between it and the modified filler, and it is easily affected by the environment to migrate and escape, so the heat aging and ultraviolet aging resistance are also significantly lower than that of Example 4. Therefore, the modified filler and anti-aging agent of the present invention play an important role in improving and maintaining the anti-aging performance of the bio-based nylon thermal insulation material.
[0059] The bio-based nylon thermal insulation materials prepared in Examples 4-6 and Comparative Examples 1-2 were cut into 1.5 cm 3 The small cubes were immersed in distilled water at 10℃ and 40℃ for 30 days respectively, and the changes in the morphology of the small cubes were observed. The test results are shown in Table 2 below:
[0060] Table 2
[0061]
[0062] It can be seen from the test results of Comparative Example 1 and Example 4 in Table 2 above that when the modified filler in Comparative Example 1 is replaced, the effect of fluorine element is lost, the hydrophobicity of the bio-based nylon thermal insulation material decreases, and the volume expansion rate increases, and the volume expansion rate further increases after the temperature rises; it can be seen from the test results of Comparative Example 2 and Example 4 that when the anti-aging agent in Comparative Example 2 is replaced, there is no chemical reaction between the modified filler in Comparative Example 2 and the replaced anti-aging agent, so the dispersion degree is reduced compared with the dispersion degree of the modified filler in Example 4, and the hydrophobicity is reduced compared with Example 4, and the volume expansion rate increases.
[0063] In summary, it can be seen from the test results in Table 1 and Table 2 that, under the combined action of the modified filler and the anti-aging agent of the present invention, the bio-based nylon thermal insulation material is endowed with excellent and stable mechanical properties, anti-aging properties and hydrophobic properties.
[0064] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0065] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A bio-based nylon thermal insulation material, characterized in that: The invention comprises the following raw materials in parts by weight: 75-85 parts of PA56, 25-35 parts of polydecane terephthalamide, 20-30 parts of modified filler, 1-2 parts of masterbatch, 0.5-1.5 parts of lubricant, 0.5-1.2 parts of anti-aging agent, and 0.1-0.2 parts of cross-linking agent; Wherein, the modified filler is prepared by the following steps: (1) Add 1-tetradecanol, sodium hydroxide solution and chloroform into a flask, heat to 75°C, add 3-perfluorooctyl-1,2-epoxypropane, react for 3 h, cool, add deionized water, separate the layers, measure the pH of the aqueous phase, dry the organic phase, filter, and distill the filtrate under reduced pressure to obtain intermediate 1; (2) After nitrogen was blown into the flask, intermediate 1, KH570, tetraisopropyl titanate and benzene were added, reacted at 90°C for 24 hours, cooled, distilled under reduced pressure, washed and dried to obtain intermediate 2; (3) Add glass fiber, hollow glass microspheres and deionized water into a flask and adjust the pH to 4; disperse the intermediate 2 in DMF and transfer it into the above flask, react at 60°C for 2h, cool, centrifuge, take the precipitate, sonicate in anhydrous ethanol, and dry to obtain a modified filler; The anti-aging agent is prepared by the following steps: S1. Add 2,4-dihydroxybenzophenone, triethylamine and chloroform into a flask under nitrogen protection, heat to 80°C, add 3-chloro-2-chloromethylpropene, react for 3h, distill under reduced pressure, purify by column chromatography, and distill under reduced pressure to obtain intermediate 3; S2. Under nitrogen protection, add N,N'-bis-(2,2,6,6-tetramethyl-4-piperidinyl)-1,6-hexanediamine, triethylamine and DMF into a flask, heat to 90°C, add 2,6-di-tert-butyl-4-bromomethylphenol, react for 3h, cool, and distill under reduced pressure to obtain intermediate 4; S3. Under nitrogen protection, add intermediate 3, pyridine and DMF into a flask, raise the temperature to 90°C, add intermediate 4, react for 4 hours, cool, and distill under reduced pressure to obtain an anti-aging agent.
2. The bio-based nylon thermal insulation material according to claim 1, characterized in that: The amount ratio of 1-tetradecanol and 3-perfluorooctyl-1,2-propylene oxide in step (1) is 25.1 g:27.8 mL; the amount ratio of intermediate 1, KH570, tetraisopropyl titanate and benzene in step (2) is 41.4 g:15.3 mL:0.05 g:200 mL; the amount ratio of glass fiber, hollow glass microspheres, intermediate 2, deionized water and DMF in step (3) is 20 g:4 g:2 g:250 mL:15 mL.
3. The bio-based nylon thermal insulation material according to claim 1, characterized in that: The amount ratio of 2,4-dihydroxybenzophenone, 3-chloro-2-chloromethylpropylene, triethylamine and chloroform in step S1 is 23 g: 11.6 mL: 14 mL: 250 mL; the amount ratio of N,N'-bis-(2,2,6,6-tetramethyl-4-piperidinyl)-1,6-hexanediamine, 2,6-di-tert-butyl-4-bromomethylphenol, triethylamine and DMF in step S2 is 39.5 g: 32.1 g: 14 mL: 240 mL; the amount ratio of intermediate 3, intermediate 4, pyridine and DMF in step S3 is 25.9 g: 49 g: 7.2 mL: 240 mL.
4. The bio-based nylon thermal insulation material according to claim 1, characterized in that: The color masterbatch is one or more of carbon black, aniline black, titanium dioxide and zinc oxide.
5. The bio-based nylon thermal insulation material according to claim 1, characterized in that: The lubricant is one or more of stearic acid, calcium stearate, zinc stearate, magnesium stearate, and ethylene bis stearamide.
6. The bio-based nylon thermal insulation material according to claim 1, characterized in that: The cross-linking agent is one or more of benzoyl peroxide, triallyl isocyanurate, dicumyl peroxide, and azobisisobutyronitrile.
7. A method for preparing the bio-based nylon thermal insulation material according to any one of claims 1 to 6, characterized in that: The following steps are involved: The raw materials are weighed by weight and put into a mixer, fully stirred until mixed evenly, and then put into a twin-screw extruder, melt-mixed and extruded to obtain a bio-based nylon thermal insulation material.
Citation Information
Patent Citations
Anti-UV (ultraviolet) nylon composite for automotive exteriors and preparation method of composite
CN106280424A
Hydrolysis and alcoholysis resistant modified nylon 66 material for automotive water chamber and preparation method of modified nylon 66 material
CN108948738A
Bio-based nylon composite material for door and window thermal insulation strips, and preparation method thereof
CN110437612A